2020
DOI: 10.25259/sni_305_2020
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary macroadenoma apoplexy in a severe acute respiratory syndrome-coronavirus-2-positive testing: Causal or casual?

Abstract: Background: In December 2019, in Wuhan, a new virus emerged, causing severe acute respiratory syndrome (SARS) secondary to infection by a type of coronavirus, causing coronavirus disease (COVID-19). The pandemic caused by the new coronavirus has had implications in the central nervous system. COVID-19 is known to be characterized by coagulation activation and endothelial dysfunction, causing ischemic and hemorrhagic vascular syndromes. Case Description: A 27-year-old male patient case with progressive decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 12 publications
1
38
0
1
Order By: Relevance
“…Chan et al [ 5 ] have recently reported a case of pituitary apoplexy associated with a third-trimester pregnancy complicated by infectious coronavirus disease 2019 (COVID-19). A few other cases [ 6-8 ] have also been reported thus far ( Table 1 ). However, in none of these cases [ 5-8 ] have the authors suggested a causal relationship between pituitary apoplexy and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection.…”
mentioning
confidence: 91%
“…Chan et al [ 5 ] have recently reported a case of pituitary apoplexy associated with a third-trimester pregnancy complicated by infectious coronavirus disease 2019 (COVID-19). A few other cases [ 6-8 ] have also been reported thus far ( Table 1 ). However, in none of these cases [ 5-8 ] have the authors suggested a causal relationship between pituitary apoplexy and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection.…”
mentioning
confidence: 91%
“…Coexistence of PA and COVID-19 infection has been previously reported [17,18]. The signi cance of this correlation is still unclear [17]. Similarly, Chan et al [18] reported another case of a patient with PA who also tested positive for COVID-19 infection, although in this case, pregnancy may have played an important role in the development of the pituitary infarction [19].…”
Section: Discussionmentioning
confidence: 88%
“…Coexistence of PA and COVID-19 infection has been previously reported [17,18]. The signi cance of this correlation is still unclear [17].…”
Section: Discussionmentioning
confidence: 95%
“…Histopathological examinations of brain specimens of patients diagnosed with COVID-19 have shown acute hypoxic injury, with loss of neurons in the absence of thrombi or vasculitis [ 3 ]. Pituitary apoplexy has been attributed to COVID-19 within recent months; however, all of these cases have identified underlying etiologies such as pituitary macroadenomas [ 4 , 5 ]. To our knowledge, this case is the first in the literature to describe pituitary apoplexy, in the absence of a pituitary macroadenoma or other identifiable causes, as a sole complication of COVID-19 infection and its subsequent cerebral hypoxic injury.…”
Section: Introductionmentioning
confidence: 99%